COMANDS AND DIVISION OF DUTIES IN THE CODES OF LAWS, DECREES AND ORDINANCES FROM 1840 AND 1845 (Heritage, 2021)
The aim of this paper is to examine commands and division of duties in the laws, decrees and ordinances from 1840 and 1845. We employed the following methods in our analysis: functional, stylistic, syntactic, linguistic, historical and discourse analysis. We have come to the conclusion that the modal verb should within the deep structure of the legal texts, ought to be expressed on the surface structure via (in)expressive means. Stern orders are connected to certain professions such as soldiers or government officials. More lenient orders and suggestions are connected with situations where the legislator is of a lower rank than the addressee. Additional expressiveness is conditioned by the lexical and semantic properties of the verbs, the use of negation, additional qualifiers and the accumulation of examples.
Keywords: historical discourse analysis, syntax, 19th century, legal discourse